The Influence of Films on Romantic Expectations of Young LGBTQ+ Men - Anthony Bilello (The Young Researcher)
This paper analyzes the influence that films featuring LGBTQ+ relationships have in fostering the romantic expectations of young LGBTQ+ men aged 15-20. The films Bohemian Rhapsody (2018) and Rent (2005) were analyzed based on how LGBTQ+ relationships were characterized, finding dramatic or unrealistic representation of physical and emotional expectations in addition to expectations of conflict resolution. This data informed a survey asking LGBTQ+ and straight men about their expectations of romance, romantic partners, and themselves in a relationship. The survey displayed a strong difference in expectations, specifically in terms of physical expectations.